1999
DOI: 10.1590/s0066-782x1999000600001
|View full text |Cite
|
Sign up to set email alerts
|

Are apolipoproteins A and B better than lipoproteins for assessing risk of obstructive coronary heart disease?

Abstract: Objective -To evaluate whether apolipoproteins A-I (Apo A-I) and B (Apo B) have, higher ensitivity (SN), specificity (SP) and positive predictive value (PPV) than lipoproteins (LP), total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL), and triglycerides (TGL) in assessing the risk of coronary heart disease (CHD). Methods - TC: R$ 9.94; HDL: R$ 21.30; LDL: R$ 28.40; TGL: R$ 14.20. One of the major scientific contributions to cardiology in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…One of the potential biomarkers of atherosclerosis analyzed in this work is ApoA1, the major protein constituent of the plasma HDL complex. Epidemiologic studies have confirmed that reduced levels of HDL and ApoA1 have a pro-atherogenic effect [ 65 , 66 , 67 ]. Our analysis showed for the first time that the relative expression of mRNA transcripts for the APOA1 gene was significantly lower both in platelets and megakaryocytes from SP MS patients compared to the control group ( Figure 4 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential biomarkers of atherosclerosis analyzed in this work is ApoA1, the major protein constituent of the plasma HDL complex. Epidemiologic studies have confirmed that reduced levels of HDL and ApoA1 have a pro-atherogenic effect [ 65 , 66 , 67 ]. Our analysis showed for the first time that the relative expression of mRNA transcripts for the APOA1 gene was significantly lower both in platelets and megakaryocytes from SP MS patients compared to the control group ( Figure 4 A,B).…”
Section: Discussionmentioning
confidence: 99%